Women Participation in Economic Devlopment - Rathore, Ruchika (Journal of Commerce and Trade, 2022)
Women have the capability to accelerate the economic growth of the country, if their participation in the workforce is increased. Census (2011) data has revealed that there has been a continuing fall in labour force participation rate of women from 33.3 per cent to 26.5 per cent in rural areas. Mainstreaming gender roles by skilling women in non-traditional roles and increasing gender sensitivity in the workplace will have a catalytic effect on productivity and be a smart economic decision. Rural women are key agents for achieving the transformational economic, environmental and social changes required for sustainable development. Empowering them is crucial not only to the well-being of individual families & rural communities, but also to overall economic productivity given women's large presence in the agricultural work force. To restore their rightful & dignified status, the present government has initiated empowerment programmes for rural women that provide a solid foundation to nurture the inner strength & self-esteem for the rural women.